Bird diversity and factors affecting bird abundance at Dullu Municipality, Dailekh, Nepal (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Shah SB, Sharma HP. 2022. Bird diversity and factors affecting bird abundance at Dullu Municipality, Dailekh, Nepal. Biodiversitas 23: 1535-1545. Bird distribution, diversity, and abundance in any ecosystem are determined by seasonality, disturbances, and availability of resources. The point count method was used for bird surveys during the winter and summer season to identify the bird diversity and factors affecting bird abundance in 2020 at Dailekh District, Nepal. Altogether 98 bird species belonging to 11 orders and 38 families were recorded. The highest species richness was found for order Passeriformes and Muscicapidae family. Among recorded species, the higher species richness of birds was found during winter than summer season, and 52 bird species were observed at both seasons. These birds were more evenly distributed in summer than in the winter season. Among 98 species, the higher bird species were resident (91%), followed by winter migrants (7%), and remaining 2% of birds were summer and passage migrants. Himalayan Vulture (Gyps himalayensis Hume, 1869) and Alexandrine Parakeet (Palaeornis eupatria Linnaeus, 1766) were near threatened species found in the study area. Forest habitats had more diverse bird species than agricultural land. Different environmental parameters such as nearest distance to the water source, canopy cover, and nearest distance to forest habitat significantly affected bird occurrences. The species richness was positively correlated with the nearest distance to agricultural land for both seasons; however, it decreased with increasing distance to water source and canopy cover. In the study area, migratory, residential, endemic, and threatened bird species indicated the uniqueness of the bird habitat in the area; therefore, a site-specific management plan is necessary to conserve these bird species.
Keywords: Abundance, bird, conservation, diversity, seasonality, threats